Mezenteric located ovarian implant syndrome: A case report - Emin ERSOY; Mustafa CÖMERT; Ercüment TEKİN and Ferit TANERİ and Sibel YENİDÜNYA and Ayşe DURSUN (Turkish Journal of Gastroenterology, 2019)
-